Future Studies: Proposed Application to Graphic Design at PUCE - Lozada-Mondragón, Mariana; Rivadeneira-Cofre, Andrea (RChD: creación y pensamiento, 2024)
This research addresses the conceptual and practical bases of future studies and their ways of insertion into graphic design processes. Understood as a key tool for visual communication in future studies, by allowing the exhibition of complex scenarios and proposals, an approach is proposed here from the teaching of this discipline that provides students with professional tools to link to new spaces for making decisions. Thus, the article recognizes future studies’ origins, evolutions, and applications and explores the methodological bases and tools used in Latin America to establish links with graphic design. From these data and the analysis of some explorations of the application of speculative, critical, and fictional design in academic spaces in Latin America, the base structure and content proposal arises for the subject of Design for the future in the Graphic Design Degree of the Pontifical Catholic University of Ecuador (puce), in order to strengthen critical, reflective, and experimental practice, along with rethinking academic teaching and the contribution of the designer to create new future scenarios.